Raining stones? Female immigrants in the Spanish labour market - Antón, José Ignacio; Muñoz de Bustillo, Rafael; Carrera, Miguel (Estudios de Economía, 2016)
The aim of this paper is to analyse how female migrants fare in the Spanish labour market, a country that has experienced impressive immigration flows during the last decade. Particularly, we explore the differential access to employment and the earning gap faced by this group, considering the interaction between two potential sources of disadvantage for migrant women: gender and migrant condition. Our findings suggest that migrant women do face this double disadvantage. In both cases, we find an economically significant gap, at least for migrants from developing countries. Regarding the former, the larger unemployment rate of female migrants is not explained by observable characteristics. In the case of earnings differential, although human capital endowments play a relevant role, both the unexplained earnings penalty associated with gender and migrant status slightly rise across the distribution of wages.